Integrating generic skills into college courses to meet the changing workforce needs - Soliman, Randa Abdou (International Journal of Psychosocial Rehabilitation, 2020)
This study addresses the issue of integrating generic skills into college courses to help meet workforce needs through an analysis of preservice teachers’ perception of their preparation at the College of Education, Teaching English as a Foreign Language (TEFL) Program. This study highlights the role of high education institutions in providing the workplaces with graduates who have transferrable skills. In this study, four sets of generic skills were embedded in preservice teachers’ courses. Descriptive statistics were used to analyse preservice teachers’ responses to a questionnaire on generic skills. Results show that they perceived their preparation as being effective in helping them develop generic skills. The highest mean (4.83) goes for the teaching/learning activities related to generic skills. The lowest mean (3.54) goes for the content of the courses. This indicates that courses content should be modified to cover generic skills in addition to discipline-specific skills. It also suggests that there is a further need to develop curricula, instructional strategies and assessment techniques that target the development of generic skills throughout the teacher preparation programs. The results of this research are expected to have an implication for individuals, educational institutions and business entities.